2017
DOI: 10.1002/jcp.26067
|View full text |Cite
|
Sign up to set email alerts
|

Ptn functions downstream of C/EBPβ to mediate the effects of cAMP on uterine stromal cell differentiation through targeting Hand2 in response to progesterone

Abstract: Ptn is a pleiotropic growth factor involving in the regulation of cellular proliferation and differentiation, but its biological function in uterine decidualization remains unknown. Here, we showed that Ptn was highly expressed in the decidual cells, and could induce the proliferation of uterine stromal cells and expression of Prl8a2 and Prl3c1 which were two well-established differentiation markers for decidualization, suggesting an important role of Ptn in decidualization. In the uterine stromal cells, proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…It has previously been reported that progesterone was essential for the differentiation of uterine stromal cells during decidualization [2, 27, 28]. As described above, progesterone could promote the expression of Hmgn2 which played an important role in stromal differentiation.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…It has previously been reported that progesterone was essential for the differentiation of uterine stromal cells during decidualization [2, 27, 28]. As described above, progesterone could promote the expression of Hmgn2 which played an important role in stromal differentiation.…”
Section: Resultsmentioning
confidence: 82%
“…Collectively, these results reveal that Hmgn2 is a critical downstream target of progesterone in regulating stromal differentiation during decidualization. Previous studies have found that progesterone induced the accumulation of Hand2 mRNA in uterine stromal cells [28, 31]. However, once transfection with Hmgn2 siRNA, the induction of Hand2 by progesterone was abolished, implying that Hmgn2 is required in the crosstalk between progesterone and Hand2.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Primer sequences were shown as follows: 5′-CCCGGATGCTTCTGTCAACT and 5′-AACGAGCCTTGTCAGCCTTT (Hmgb1); 5′-CACCGGATCTAGACATGCCC and 5′-ACGTCTGTGGAACAGCAGAG (Klf5); 5′-CGCAGCTTCCATCACGAA and 5′-CACTGGGGACAGAACTTAAA (Bmp2). The other primer sequences used in this study were described previously [16].…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Hybridization was performed as described previously [16]. Sections were counterstained with 1% methyl green.…”
Section: In Situ Hybridizationmentioning
confidence: 99%